2019
DOI: 10.1007/s13201-019-1121-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cationic surfactant-modified kaolin for enhanced adsorption of hexavalent chromium from aqueous solution

Abstract: In the current work, we have reported a cationic surfactant-modified Ethiopian kaolin for improved adsorption of Cr(VI) from aqueous solution. The raw kaolin was modified by treating with CTAB to enhance the adsorption properties. The crystal structure and vibrational analysis of CTAB-kaolin were investigated by Fourier transform infrared spectroscopy (FTIR) and powder X-ray diffraction (p-XRD) techniques. The successful modification of kaolin by CTAB through intercalation and coating was investigated by XRD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…This study was examined over a concentration range of 10–100 mg g −1 with a fixed adsorbent dose of 0.25 g. As shown in Fig. 11 , the result revealed that the uptake capacities of PQ and Q increased from 2.5 to 24.3 mg g −1 and 5.1 to 44.0 mg g −1 respectively as the initial Cr(VI) concentration increased from 10 to 100 mg dm −3 at 298 K. It indicated that the adsorptive removal of Cr(VI) onto PQ and Q was strappingly dependent on the initial hexavalent chromium concentration 68 . The phenomenon could be associated with enhanced collisions frequency between the Cr(VI) ions and the adsorption sites on the surface PQ and Q, resulting in higher surface coverage at high initial Cr(VI) concentrations, and thus high uptake capacities.…”
Section: Resultsmentioning
confidence: 83%
“…This study was examined over a concentration range of 10–100 mg g −1 with a fixed adsorbent dose of 0.25 g. As shown in Fig. 11 , the result revealed that the uptake capacities of PQ and Q increased from 2.5 to 24.3 mg g −1 and 5.1 to 44.0 mg g −1 respectively as the initial Cr(VI) concentration increased from 10 to 100 mg dm −3 at 298 K. It indicated that the adsorptive removal of Cr(VI) onto PQ and Q was strappingly dependent on the initial hexavalent chromium concentration 68 . The phenomenon could be associated with enhanced collisions frequency between the Cr(VI) ions and the adsorption sites on the surface PQ and Q, resulting in higher surface coverage at high initial Cr(VI) concentrations, and thus high uptake capacities.…”
Section: Resultsmentioning
confidence: 83%
“…The spectrum of MoS 2 NSs shows the broad bands between 3748 and 3400 cm −1 attribute to the characteristics of O–H stretching of the intermolecular and intramolecular hydrogen bonds. 44,45 The characteristic vibrational bands at 3300–2800 cm −1 and 1488 cm −1 can be assigned to the stretching of the C–H alkyl stretching band in l -cysteine. 46 Thus, the FTIR results further affirmed the presence of residual amino acid on the surface of MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of MoS 2 NSs shows the broad bands between 3748 and 3400 cm À1 attribute to the characteristics of O-H stretching of the intermolecular and intramolecular hydrogen bonds. 44,45 The characteristic vibrational Fig. 2 The UV-Vis absorption spectrum of MoS 2 NSs.…”
Section: Characterizations Of Mos 2 Nanosheetsmentioning
confidence: 99%
“…Kaolin was activated by H 2 SO 4 based on a protocol reported in previous work. 34,35 Particularly, the raw kaolin sample was purified by washing with distilled water 3 times followed by drying in an oven at 105°C for 3 hours. The dried sample was crushed to obtain a fine powder that was able to pass through a 63-μm mesh size sieve.…”
Section: Methodsmentioning
confidence: 99%